U-Shaped Relationship of Non-HDL Cholesterol With All-Cause and Cardiovascular Mortality in Men Without Statin Therapy - Zeng, Rui-Xiang; Xu, Jun-Peng; Kong, Yong-Jie; Tan, Jia-Wei; Guo, Li-Heng; Zhang, Min-Zhou (Frontiers in Cardiovascular Medicine, 2022)
Background Non-HDL-C is well established causal risk factor for the progression of atherosclerotic cardiovascular disease. However, there remains a controversial pattern of how non-HDL-C relates to all-cause and cardiovascular mortality, and the concentration of non-HDL-C where the risk of mortality is lowest is not defined. Methods A population-based cohort study using data from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2014. Male participants without statin therapy were divided into the six groups according to non-HDL-C levels (<100, 100–129, 130–159, 160–189, 190–219, ≥220 mg/dl). Multivariable Cox proportional hazards models were conducted with a hazard ratio (HR) and corresponding 95% confidence interval (CI). To further explore the relationship between non-HDL-C and mortality, Kaplan–Meier survival curves, restricted cubic spline curves, and subgroup analysis were performed. Results Among 12,574 individuals (average age 44.29 ± 16.37 years), 1,174(9.34%) deaths during a median follow-up 98.38 months. Both low and high non-HDL-C levels were significantly associated with increased risk of all-cause and cardiovascular mortality, indicating a U-shaped association. Threshold values were detected at 144 mg/dl for all-cause mortality and 142 mg/dl for cardiovascular mortality. Below the threshold, per 30 mg/dl increase in non-HDL-C reduced a 28 and 40% increased risk of all-cause (p < 0.0001) and cardiovascular mortality (p = 0.0037), respectively. Inversely, above the threshold, per 30 mg/dl increase in non-HDL-C accelerated risk of both all-cause mortality (HR 1.11, 95% CI 1.03–1.20, p = 0.0057) and cardiovascular mortality (HR 1.30, 95% CI 1.09–1.54, p = 0.0028). Conclusions Non-HDL-C was U-shaped related to all-cause and cardiovascular mortality among men without statin therapy.